2013
DOI: 10.1152/ajprenal.00300.2012
|View full text |Cite
|
Sign up to set email alerts
|

Renal ammonia excretion in response to hypokalemia: effect of collecting duct-specific Rh C glycoprotein deletion

Abstract: Lee HW, Verlander JW, Bishop JM, Handlogten ME, Han KH, Weiner ID. Renal ammonia excretion in response to hypokalemia: effect of collecting duct-specific Rh C glycoprotein deletion. Am J Physiol Renal Physiol 304: F410 -F421, 2013. First published December 5, 2012; doi:10.1152/ajprenal.00300.2012.-The Rhesus factor protein, Rh C glycoprotein (Rhcg), is an ammonia transporter whose expression in the collecting duct is necessary for normal ammonia excretion both in basal conditions and in response to metabolic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Gels were then transferred electrophoretically to nitrocellulose membranes. We confirmed that protein loading and transfer efficiency did not differ significantly between samples using Ponceau S staining, as we have previously described (1,2,16,33,35,36). Membranes were then blocked with 5 g/dl nonfat dry milk in Blotto buffer (50 mM Tris, 150 mM NaCl, 5 mM Na 2EDTA, and 0.05% Tween 20; pH 7.6) and incubated at 4°C overnight with primary antibody diluted in nonfat dry milk.…”
Section: Animalssupporting
confidence: 83%
“…Gels were then transferred electrophoretically to nitrocellulose membranes. We confirmed that protein loading and transfer efficiency did not differ significantly between samples using Ponceau S staining, as we have previously described (1,2,16,33,35,36). Membranes were then blocked with 5 g/dl nonfat dry milk in Blotto buffer (50 mM Tris, 150 mM NaCl, 5 mM Na 2EDTA, and 0.05% Tween 20; pH 7.6) and incubated at 4°C overnight with primary antibody diluted in nonfat dry milk.…”
Section: Animalssupporting
confidence: 83%
“…We generated these mice using Cre-loxP techniques, using mice with floxed Rhbg genes we characterized previously (2, 3) and using mice expressing Cre-recombinase under control of the Ksp-cadherin promoter (14,29). In previous studies examining Rhcg, we showed that the Ksp-cadherin promoter yields collecting duct-specific gene deletion (19,21). Examination of mice homozygous for floxed Rhbg alleles and expressing Ksp-cadherin-Cre using mouse Rhbg-specific antibodies confirmed collecting duct-specific Rhbg deletion.…”
Section: Resultsmentioning
confidence: 99%
“…Mice with floxed Rhbg gene generated in our laboratory and described previously (2, 3) and expressing Cre-recombinase under control of the Ksp-cadherin promoter (19,21,29) were used to generate mice with collecting duct-specific Rhbg knockout (CD-Rhbg-KO). Littermates that did not express Cre-recombinase were used as control mice.…”
Section: Antibodiesmentioning
confidence: 99%
“…Hypokalemia increases Rhcg expression, consistent with Rhcg having an important role in the increased ammonia excretion. However, the pattern of changes differs from those seen with metabolic acidosis (8,34,58). Rhcg expression increases in OMCD intercalated cells, where there is more discrete apical Rhcg expression in intercalated cells and a marked increase in apical plasma membrane immunolabel compared with control animals (34).…”
Section: Role Of Rh Glycoproteins In Renal Ammonia Excretionmentioning
confidence: 90%